2017
DOI: 10.1021/acs.est.7b02488
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Emerging Per- and Polyfluoroalkyl Substances (PFASs) in River and Drinking Water near a Fluorochemical Production Plant in the Netherlands

Abstract: The present study investigated the presence of legacy and emerging per- and polyfluoroalkyl substances (PFASs) in river water collected in 2016 up- and downstream from a fluorochemical production plant, as well as in river water from control sites, in The Netherlands. Additionally, drinking water samples were collected from municipalities in the vicinity from the production plant, as well as in other regions in The Netherlands. The PFOA replacement chemical GenX was detected at all downstream river sampling si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
215
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 311 publications
(219 citation statements)
references
References 22 publications
2
215
2
Order By: Relevance
“…With the growing body of literature on PFAS health effects, pooled and meta-analyses might be possible and would increase statistical power to address the potential toxicity of these compounds. Finally, some fluorinated compounds that have recently replaced PFOS and PFOA in manufacturing processes and that are currently detected in humans and the biota [16] deserve attention and need to be considered in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the growing body of literature on PFAS health effects, pooled and meta-analyses might be possible and would increase statistical power to address the potential toxicity of these compounds. Finally, some fluorinated compounds that have recently replaced PFOS and PFOA in manufacturing processes and that are currently detected in humans and the biota [16] deserve attention and need to be considered in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA), the two most widely detected PFASs, have decreased in some countries following a drop in production since the year 2000 [11, 12], but exposure to other short-chain and also some long-chain PFASs are increasing in many countries [13]. In addition, some new fluorinated compounds that are used to replace PFOS have also recently been detected in biota [1416]. …”
Section: Introductionmentioning
confidence: 99%
“…The entire sample (containing methanol and IS) was filtered through a GF/A filter (1.7 μm pore size) into an HDPE vacuum flask and the filtrate returned to the original sample bottle. For solid‐phase extraction (SPE), a 500 mL aliquot was removed from the sample bottle and processed through a weak anion‐exchange (WAX), reverse‐phase, water‐wettable polymer cartridge (Gebbink et al , Heydebreck et al , Strynar et al ). WAX cartridges improve the recovery of GenX and other PFEAs compared with the styrene–divinylbenzene SPE cartridges recommended in USEPA Method 537.…”
Section: Methodsmentioning
confidence: 99%
“…Strynar et al () first identified GenX along with other PFEAs (Table ) in US surface waters, and Sun et al () reported GenX concentrations of up to 4,560 ng/L in the Cape Fear River of North Carolina. Most recently, Gebbink et al () conducted a detailed study of the Rhine River near a fluorochemical manufacturing facility in the Netherlands and determined a maximum GenX concentration of 812 ng/L at the first sampling location downstream of the manufacturing plant.…”
Section: Occurrence Of Genx and Related Compoundsmentioning
confidence: 99%
See 1 more Smart Citation